Environmental effects on cognition and decision making of knowledge workers. (April 2017) - Moskaliuk, Johannes; Burmeister, Carolin P.; Landkammer, Florian; Renner, Bettina; Cress, Ulrike
Abstract: The term ubiquitous working describes the relocation from working in a traditional office on company premises to flexible working in the home or in other environments that were never originally conceptualized for working, such as parks or hotel lobbies. Research indicates that the environment has the potential to influence work performance. We used virtual 3D environments to examine the impact of a work-related (characteristic office) vs. a non-work related context (Tuscan garden) on attention, concentration, and decision making. We assumed that the context would influence cognitive performance. Our results showed that, compared to the non-work context, participants in the work context (1) had marginally faster reaction times in an attentional task (2) were more accurate in completing a concentration test, and (3) made decisions that were more risky. These results suggest that working in a more typical work environment enhances work performance and influences decision making. Highlights: Mobile devices enable ubiquitous working in multiple, varying environments. Exploring a virtual environment affects work performance. Being in a work-related context leads to a more risky decision-making behaviour. Being in a work-related context enhances efficiency in a concentration task.